Redação de vestibular: sujeitos e ensino em pré-vestibulares noturnos de Recife - Freitas, Renan Luiz de (2006)
This study looks into the teaching of text production in evening courses which aim to prepare students for the university entrance exams (known as vestibular ), and which are offered by three private teaching institutions in Recife. Its main objective is to contrast the teaching of essay writing with the heterogeneity of the subjects who enroll for such courses. Specific objectives involve, first and foremost, comparing the quality of teaching in the three institutions and, secondly, to investigate the extent to which such teaching enables these subjects to produce competitive texts in which they also present themselves as the authors of their own production (PILAR, 2005, POSSENTI, 1999; BRONCKART, 1999). This is a field and documental study. We have collected two types of documents from the teaching institutions: The enrolment forms and the lesson notes. The data extracted from such documents is the basis of our analysis. From the enrolment forms we have collected possible traits from the subjects social-economical profile. Our aim here was to investigate how far the teaching of essay writing could cater for the heterogeneity of profiles in these classrooms. We also aimed to investigate, from the lesson notes, whether the teaching methods implied in the contents of such notes would actually provide the subjects with the right tools for text production. More specifically the production of a text which meets the standard required by the university entrance exams (vestibular) examining board, and which enables subjects to present themselves as the authors of their own production as stated by Pilar (2005), for instance. Results point to structural problems (administrative ones, human resources, methodological and didactic resources) which affect attention to heterogeneity. Consequently, no text productions is promoted, nor is teaching effective, process-oriented, progressive, and catering to the different subjects needs. On the positive side, we notice that the activities focus on the text as a starting point and merely metalinguistic interventions have had little room in the classroom. What is more, we could also see, albeit discretely, activities in which important scientific contributions relating to the teaching of text production are embedded. In sum, we can conclude that the teaching of text production in preparation courses for the university entrance exams requires, in the first place, a change in the way these courses address their target audience, and, secondly, an urgent insertion of what Science has produced in the area of meeting individual needs. We believe that, by providing subjects with the ability to produce discursive texts, there will be more chances of ascension and inclusion of these subjects in the cultural heritage, and in a system that is more and more surrounded and organized by genres of written and oral texts (BAZERMAN, 2005; GNERRE, 1998; OLSON, 1997)